MiR-191 is involved in renal dysfunction in arsenic-exposed populations by regulating inflammatory response caused by arsenic from burning arsenic-contaminated coal. (January 2020) - Xu, Y; Zou, Z; Liu, Y; Wang, Q; Sun, B; Zeng, Q; Liu, Q; Zhang, A
Chronic exposure to arsenic may result in the manifestation of damage in multiple organs or systems of the body. Arsenic-induced renal dysfunction has been determined, but their pathogenesis has not been fully examined. In this study, we measured the expression levels of miR-191 in plasma, the contents of pro-inflammatory (interleukin (IL)-6 and tumor necrosis factor alpha) and anti-inflammatory (IL-2 and transforming growth factor beta) cytokines, and renal dysfunction indicators (blood urea nitrogen, blood creatinine, uric acid, and cystatin C) in serum from control and arsenic poisoning populations and analyzed the relationship between the miR-191, cytokines, and renal dysfunction indicators. The results clearly show the alteration of miR-191 expression was significantly associated with arsenic-induced renal dysfunction. Overall, the association of miR-191, inflammatory response and renal dysfunction, is clearly supported by the current findings. In other words, miR-191 is involved in renal dysfunction in exposed populations by regulating inflammatory response caused by coal-burning arsenic. The study provides a scientific basis for further studies of the causes of the arsenic-induced renal dysfunction, the biological role of miR-191, and targeted prevention strategies.